Uncovering the Modulatory Interactions of Brain Networks in Cognition with Central Thalamic Deep Brain Stimulation Using Functional Magnetic Resonance Imaging. (1st August 2020) - Li, Ssu-Ju; Lo, Yu-Chun; Lai, Hsin-Yi; Lin, Sheng-Huang; Lin, Hui-Ching; Lin, Ting-Chun; Chang, Ching-Wen; Chen, Ting-Chieh; Chin-Jung Hsieh, Christine; Yang, Shih-Hung; Chiu, Feng-Mao; Kuo, Chao-Hung; et al.
Highlights: CT-DBS increases in the functional connectivity of the corticostriatal, corticolimbic, and thalamocortical networks. CT-DBS enhances the cognitive function of learning and memory. Changes in the dopamine receptors after CT-DBS suggest that CT-DBS alters the synapse plasticity. Abstract: Deep brain stimulation (DBS) is a promising treatment for neurological and psychiatric disorders. It acts by altering brain networks and facilitating synaptic plasticity. For enhancing cognitive functions, the central thalamus (CT) has been shown to be a potential DBS target. The network-level mechanisms contributing to the effect exerted by DBS on the CT (CT-DBS) remain unknown. Combining CT-DBS with functional magnetic resonance imaging (fMRI), this study explored brain areas activated while applying CT-DBS in rats, using a newly developed neural probe that was compatible with MRI and could minimize the image distortion and resolve safety issues. Results showed activation of the anterior cingulate cortex, motor cortex, primary and secondary somatosensory cortices, caudate putamen, hypothalamus, thalamus, and hippocampus, suggesting that the corticostriatal, corticolimbic, and thalamocortical brain networks were affected. Behaviorally, the CT-DBS group required a shorter time than sham controls to learn a water-reward lever-pressing task and made more correct choices in a T-maze task. Concurrent with enhanced learning performance, bilateral CT-DBS resulted in alteration in the functional connectivity of brain networks determined by resting-state fMRI. Western blot analyses showed that the protein level of both dopamine D1 and α4-nicotinic acetylcholine receptors was increased, and dopamine D2 receptor was decreased. These data suggest that CT-DBS can enhance cognitive performance as well as brain connectivity through the modulation of synaptic plasticity, such that CT is a target providing high potential for the remediation of acquired cognitive learning and memory disabilities.